Value and quality creation: natural resources, industrialization and standards of living in peru 1950 to 1997 - Roca , Santiago (1999)
Peru”s recent economic policy, like that of most Latin American countries! has followed the paradigm of the socalled “Washington Consensus”. Such paradigm precludes the implementation of “strategic” industrial policies as well as the active and deliberate construction of competitive advantages through measures that foster certain sectors or activities. “Washington-Consensus” thinkers hold that the “magic of the market” and its indiscriminate opening will allow countries to acquire the necessary long-term external competitiveness, promote economic growth and enhance standards of living, regardless of the country”s productive specialization.